The effect of essential plant oils on mineral composition of egg mass and blood parameters of laying hens - Róbert HERKEĽ (Journal of Central European Agriculture, 2016)
The aim of study was to analyze the dietary effect of pumpkin and flaxseed oils on mineral composition of egg mass and blood parameters of laying hens. At 38 weeks of age, Lohmann Brown Lite hens were housed in three-floor cages, divided into three dietary groups (C-control, E1-pumpkin oil (3%), E2-flaxseed oil (3%)). There were housed six hens in one cage. A total 18 hens were monitored. In the control group hens were fed with standard complete feed mixture for laying hens and in the experimental groups by feed mixtures with supplementation of pumpkin or flaxseed oils. Vitamin E was added into feed mixture in the experimental groups. The experiment lasted 52 days. Twelve eggs from each dietary treatment were randomly selected and analyzed. As regards the mineral composition of eggs, only concentrations of calcium after both oil supplementations and zinc after flaxseed oil supplementation in diet were significantly (P<0.05) higher in yolk. Contents of magnesium in yolk and albumen and phosphorus in albumen were markedly (P<0.05) lower in E1 and E2 compared to the control. Also lower (P<0.05) concentrations of potassium after flaxseed oil supplementation in yolk and zinc after both oil supplementation in albumen compared to the control were found. The amounts of other minerals were relatively balanced among groups. Significant (P<0.05) differences among groups in blood parameters of laying hens were observed in mineral and energy profile. Higher (P<0.05) concentrations of calcium, triglycerides and cholesterol in both experimental groups in comparison with control group were found in blood serum of laying hens. The supplementation of oils in diets of laying hens had not notable (P>0.05) influence on enzymatic and protein profile.